Unraveling the dynamics of loneliness in the Baltic-Nordic region: a comparative analysis in the wake of COVID-19 - Reine, Ieva; Miķelsone, Madara; Tomsone, Signe; Guðmundsson, Helgi; Ivanovs, Andrejs; Guðmundsson, Halldór S.; Koroļeva, Ilze (Frontiers in Public Health, 2024)
Introduction The primary aim of this study is to thoroughly investigate the prevalence and determinants of loneliness among older adults in the Baltic-Nordic region. Utilizing high-quality data sources and employing a methodologically rigorous approach, the study endeavors to enhance our understanding of how loneliness manifests and varies across different cultural and socio-economic contexts within these regions. By identifying key factors influencing loneliness, including demographic, social, and economic variables, the research seeks to contribute significantly to the existing body of knowledge on loneliness and inform targeted public health strategies and interventions tailored to the unique needs of older adults in the Baltic and Nordic countries. Material and methods This research, centered on older adults aged 67 and above within the Baltic-Nordic region, draws upon data from the Survey of Health, Ageing and Retirement in Europe (SHARE), specifically its eighth wave conducted between June and August 2020. The demographic analysis of this study covers a diverse sample of 5,313 participants from the Baltic and Nordic regions. Specifically, the sample includes 2,377 participants from Nordic countries, namely Sweden, Denmark, and Finland, and 2,936 from the Baltic countries of Estonia, Latvia, and Lithuania. The investigation extends to the financial well-being of households, involving an analysis of 3,925 individuals, with 1,748 from Nordic countries and 2,177 from Baltic countries. Although Iceland is categorized as a Nordic country, the analysis within this study is conducted separately due to the unavailability of SHARE data for this region. Instead, the HL20 study, focusing on the health and well-being of the older adult population in Iceland, contributes data for 1,033 respondents. This methodological distinction allows for a comprehensive understanding of regional differences, highlighting the importance of specialized approaches to examine the intricate dynamics of loneliness and well-being across the Baltic-Nordic region. Results The study reveals significant regional variations in loneliness among older adults during the COVID-19 outbreak, with the Baltic countries (Estonia, Latvia, Lithuania) reporting a lower prevalence of loneliness compared to the Nordic countries (Sweden, Denmark, Finland). Iceland, while grouped with the Nordic countries, was analysed separately. Employment emerges as a key factor in reducing loneliness across all regions, suggesting the benefits of social interactions and structured routines. Gender and marital status significantly influence loneliness, with notable disparities in the Baltic region and smaller gaps in the Nordic countries, reflecting the impact of societal and cultural norms. Additionally, educational attainment and health status show varied associations with loneliness, highlighting the complex interplay of individual and societal factors in these regions.